Case Report: Donor-derived herpes simplex virus type 1 hepatitis in a kidney transplant recipient with fatal outcome - Lindahl, Jørn Petter; Dörje, Christina; Kro, Grete Birkeland; Grzyb, Krzyztof; Hugenschmidt, Harald; Hov, Johannes Espolin Roksund; Barratt-Due, Andreas; Midtvedt, Karsten (Frontiers in Transplantation, 2025)
Current screening practices have significantly reduced the transmission of donor-derived infections through organ transplantations. However, in exceptional cases, a deceased donor may harbor an undetected active infection, or abnormal blood test results may be mistakenly attributed to the dying process, resulting in missed infections. These ongoing infections can then be transmitted through the grafts. This report presents a case of confirmed donor-derived herpes simplex virus type 1 (HSV-1) hepatitis following kidney transplantation. The HSV-1 infection in the recipient was initially overlooked and misattributed to a probable mycophenolate mofetil-induced etiology, which led to a delay in initiating antiviral therapy. The recipient subsequently developed HSV-1 hepatitis, which progressed to liver failure and multiorgan failure, ultimately resulting in death. As a result of this case, our transplant center promptly revised its screening and prophylactic antiviral treatment protocols. All kidney transplant recipients who are herpes simplex virus (HSV) antibody-negative now receive valaciclovir until the donor's HSV DNA PCR status is confirmed to be negative.